Development of academic achievements using inquiry-based learning together with educational games - Naruemon Sitthikrai; Chulida Hemtasin; Tawan Thongsuk (Intelektual Pustaka Media Utama, 2023)
The objectives of this action research were: i) To develop learning achievement in basic science subjects of grade 8 students who received an inquiry-based learning (IBL) management system combined with an educational game on the topic of solutions to pass the requirement of 70%; and ii) To study the satisfaction of grade 8 students toward the use of IBL together with an educational game. This was a classroom action research study with a target group consisting of 14 grade 8 students in the first semester of the 2022 academic year in a public school located in Northeast Thailand. The research tools were eight learning management plans, an IBL questionnaire, an educational game about the solution, a learning achievement test, an interview form, and a satisfaction questionnaire. The statistics used were mean, standard deviation, and percentage. The result showed that the mean was 14.93, and the standard deviation was 1.44, which passed the criteria of 70%, which is in the level of satisfaction.